Perencanaan Sistem Distribusi Air Minum Di Kecamatan Bangkinang, Kabupaten Kampar - Alfi Aulia Rahman; Jecky Asmura; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The need for drinking water in Bangkinang District, Kampar Regency comes from wells, river water and tap water, the quality and quantity of which are not guaranteed. The community's water needs will reach 191.61 L/s in 2039, so it is necessary to plan a drinking water distribution system with raw water sources coming from the Kampar River. drinking water distribution piping network planning is made using EPANET 2.0 software. The simulation results show that the hydraulic condition of the piping for the planning area at peak hours has a speed of 0.30 m/s – 4.06 m/s, a pressure of 8.57 m – 61.59 m, and the highest pressure loss is 4.35 m/km. The budget for the distribution piping system costs Rp. 99.844.000.000,-Key Words: Bangkinang, EPANET 2.0, Kampar River, Piping, Simulation, Water requiremen